Adults’ Adherence to Growth Hormone Replacement in Relation to Medication-Related Beliefs, Coping and Quality of Life - An Exploratory Analysis - Siegel, Sonja; Unger, Nicole; Streetz-van der Werf, Christine; Karges, Wolfram; Schilbach, Katharina; Schröder, Bernadette; Szybowicz, Janine; Sauerwald, Janina; Zopf, Kathrin; Grzywotz, Agnieszka; Bidlingmaier, Martin; Kirstein, Cedric; et al. (Frontiers in Endocrinology, 2021)
Introduction: Little is known about psychological reasons associated with adherence to growth hormone (GH) replacement therapy (GHRx) in adults. As in other chronic diseases, medication-related beliefs, coping strategies and disease impact on quality of life (QoL) might play an important role. We thus explored these psychological factors in relation to adherence in patients with GH deficiency (GHD) in order to find leverage points for the improvement of adherence. Patients and methods: Cross-sectional analysis including 107 adult GHD patients on GHRx who completed self-assessment inventories on health-related QoL (Short-Form SF-36), coping style (Freiburg questionnaire on coping with illness, FKV-LIS) and medication beliefs (Beliefs about Medicine questionnaire, BMQ). Results were correlated to general and GH-specific adherence to medication. Results: In the BMQ, 92.5% of the patients (n=99) reported a strong belief in the need for their medication, which correlated significantly with general adherence (rs = 0.325). Active coping was significantly related to general (rs = 0.307) and GH-specific adherence (rs = 0.226). Better mental QoL (rs = 0.210) but worse physical QoL (rs = -0.198; all p < 0.05) were related to higher GH-specific adherence. Older age was associated with a higher degree of active coping, a higher belief in the necessity of medication and worse physical QoL. Conclusion: We provide preliminary data that most GHD patients on GHRx are strongly convinced of their need for medication and that adherence to GHRx is influenced by coping strategies and QoL. Patients with impaired psychological QoL are less able to translate their convictions into good adherence, a phenomenon to be addressed in future research.